2021
DOI: 10.3390/cells10102575
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA and Exercise: Implications for Health and Injuries in Sports

Abstract: Recently, several studies have highlighted the tight connection between mitochondria and physical activity. Mitochondrial functions are important in high-demanding metabolic activities, such as endurance sports. Moreover, regular training positively affects metabolic health by increasing mitochondrial oxidative capacity and regulating glucose metabolism. Exercise could have multiple effects, also on the mitochondrial DNA (mtDNA) and vice versa; some studies have investigated how mtDNA polymorphisms can affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 114 publications
1
8
0
Order By: Relevance
“…Moreover, these haplogroups have been found to be abundant among power and team sports athletes [11,33,34], whose performance relies more on anaerobic glycolysis rather than OXPHOS. Similar associations with mtDNA haplogroups have also been detected among Kenyan and Japanese athletes, as reviewed in [35].…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, these haplogroups have been found to be abundant among power and team sports athletes [11,33,34], whose performance relies more on anaerobic glycolysis rather than OXPHOS. Similar associations with mtDNA haplogroups have also been detected among Kenyan and Japanese athletes, as reviewed in [35].…”
Section: Discussionsupporting
confidence: 70%
“…The increased ability to perform endurance exercise is strongly supported by enhanced mitochondrial function as suggested by increased mitochondrial gene expression, mitochondrial desoxyribonucleic acid (DNA), and mitochondrial enzyme activity [1]. Genetic and epigenetic factors may modulate adaptive responses to exercise through different mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports suggest that one or more WBC sessions can induce anti-inflammatory effects (4). In a previous study, we analysed a large panel of cytokines, haematological, and hormonal parameters, as well as circulating mitochondrial DNA (1,5). We found that in non-professional athletes, WBC induced beneficial immunological and metabolic responses and seems to promote tissue repair (1).…”
Section: Introductionmentioning
confidence: 82%